Health shocks and the added worker effect: A life cycle approach - Carlos H. Acu\~na; Hector Acu\~na; Diego Carrasco (Journal of Applied Economics, 2019)
This study analyzes the existence of the added worker effect (AWE) when a male partner suffers a health shock (negative health event), by using the information from the Chilean Social Protection Survey. The health shocks considered in this study are new cases of arthritis, asthma and hypertension. We find that neither asthma nor hypertension diagnosis generates an AWE. In the case of arthritis, the study shows differentiated effects by age cohorts. More specifically, we find that women's probability of labor force entry over three years increases by 50 percentage points when the husband between the ages of 18-44 is diagnosed with arthritis. This effect disappears in older age groups, which suggests that when studying the effect of health shocks, the differences between life cycle stages should be considered (chronic disabling conditions are an important source of financial risk for young households).
Keywords: 330; added worker effect; arthritis; asthma; Health shocks; hypertension; life cycle